Synchronous tonsillar tumors with differing histopathology: A case report and review of the literature. Issue 9 (14th March 2022) - Rossi, Nicholas A.; Reddy, Devin N.; Rawl, Jordan W.; Dong, Jianli; Qiu, Suimin; Clement, Cecilia G.; Resto, Vicente A.; Joshi, Rohan; McKinnon, Brian; Coblens, Orly
Abstract: Background: Tonsillar squamous cell carcinoma (TSCC) due to human papillomavirus (HPV) infection has seen a dramatic increase in recent years. Bilateral tonsillar squamous cell carcinoma (biTSCC) has a much lower incidence than unilateral TSCC and three main hypotheses of biTSCC pathogenesis prevail: field carcinogenesis, single‐clone, and multiple HPV infections. Case: A 49‐year‐old Male with a remote history of chewing tobacco presented with symptoms of spitting up tissue and occasional hemoptysis. Physical exam showed a sole left tonsillar mass which was confirmed to be TSCC on biopsy. The patient's computed tomographic (CT) scan was consistent with this finding; however, positron emission tomography (PET) scan indicated a second tumor in the contralateral right tonsil. Surgical resection of both masses and selective neck dissection was performed, and the specimens were sent for further pathological analysis. No complications of surgery were noted and the final diagnosis of synchronous biTSCC was made. The tumors were a T2N0M0 left poorly differentiated TSCC (p16+, EGFR+, bcl2+) with basaloid features, and a T1N0M0 right well to moderately differentiated TSCC (p16+, EGFR+, bcl2−). Conclusion: Our present case was notable for differing tumor pathology and karyotype analysis between the right and left masses, directly supporting the multiple HPV infections hypothesis of biTSCC pathogenesis. Further genetic characterization of tonsillar tumors is needed to better characterize TSCC and best guide medical/surgical therapy.